Letter (copy) : Position in the Basque Country - Citrine, Walter, 1887-1983
012b-0032-001 Secretary's. WMC/HVT/FC/539. 19th June, 1939. Senor J. I. de Lizaso, Basque Delegation, 14, Eccleston Square, S.W.1. Dear Senor Lizaso, POSITION IN THE BASQUE COUNTRY Many thanks for your letter of the 16th instant enclosing further information in regard to the position in the Basque country, for which I am greatly obliged. Yours sincerely, General Secretary. 292/946/12b/32